Zollinger - Ellison Syndrome.: Two new Cases in Uruguay - Díaz, Federico; Praderi, Raúl; Pignata, Daniel; Ferraz, Judith; Touya, Eduardo; Rubinstein, Juan P (Cirugía del Uruguay, 1980)
The authors add two new cases to the